ESSENTIAL CHARACTERISTICS OF THE FITNESS CONCEPT AND THE AREA OF FITNESS IN LATVIA AND THE WORLD - Cuprika, Aleksandra; Fernate, Andra; Cupriks, Leonids (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Despite the great popularity of fitness around the world, it is still unclear what fitness is and how people understand it. The essence of fitness has gradually evolved from simple physical fitness to a cultural phenomenon. The second path of fitness development is from the physical health of a person reflected in a person’s readiness to do physical work to the desire to improve their own quality of life. That is why the aim of this study was to investigate in depth the essential characteristics of the fitness concept and the area of fitness. The study is based on 41 literature sources and scientific articles, 8 of which are in Russian and 33 – in English. The essence of the content of the fitness concept has been investigated and the hierarchy of concepts has been evaluated in different theoretical contexts, starting from the historical beginning of the fitness concept. Definitions were grouped in a broader and a narrower sense: 1) fitness as a set of attributes and abilities and 2) fitness as a way of life, lifestyle and quality of life. The essential categories of the fitness concept were compiled. The change of fitness area and its influence on the society was discussed. By summarizing the analysis of fitness definitions and evaluating fitness according to various theoretical aspects, it can be concluded that fitness is interpreted as sport competition fitness, as an implementation of a healthy way of life and as physical fitness or health-oriented physical fitness. Due to constant change and improvement of the body ideal sometimes it is complicated to participate in the process of improving health, also achieving it requires a lot of energy and time. People don’t understand where is the difference between healthy body and fitness body prepared for competition or commercial. Therefore the greater the beauty industry and fitness area becomes, the weaker becomes the human.